Analisis Pengaruh Ekuitas Merek terhadap Keputusan Pembelian Susu Oat Merek Oatside oleh Mahasiswa Universitas Diponegoro - Ningrum, Hesty Wahyu; Setiyawan, Hery; Prasetyo, Edy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Oatside brand oat milk is a plant-based animal product alternatives (PBAPAs) that are still very popular among the public because it offers many benefits for the health of the body and the environment without reducing the delicious taste of consuming milk. This study aimed to analyze the purchasing decision making process that influence of brand equity which includes brand awareness, brand association, quality perception, and brand loyalty on the consumer decision in purchasing Oatside brand oat milk on students university of Diponegoro. This research was conducted from November to December 2024. The research method used was the survey method. The sampling method used was accidental sampling. The sample size was determined using Issac and Michael so that have a 269 respondents were taken. The data collected consisted of primary data through interviews based on G-form questionnaires, meanwhile secondary data were obtained from various relevant literature sources. The data analysis method was descriptive analysis and statistical analysis using logistic regression analysis. The result at this research showed that simultaneously brand awareness, brand associations, perceived quality and brand loyalty have significant effect on purchase decisions. The factors of brand loyalty that have a partially significant effect on purchasing decisions on students university of Diponegoro.